Problems and Strategies for Learning The Indonesian Language in Grade 2 of Yapita Elementary School, Surabaya City - Farisia, Hernik; Maulidiyah, Hilda Khilmatul; Ismiyah, Kiki Nadhifatul; Maharani, Krisnina; Roichatuzzuhriyah (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
Language can be used to communicate and become an identity in a country. Indonesian language learning is important to implement starting from the lower grades of elementary school. Language skills need to be mastered by students, such as listening, viewing, speaking, reading, and writing. Learners are taught to apply Indonesian well. On the other hand, a problem in the learning process often arises, causing learning to be disrupted. These problems can arise from educators or students. This study aims to determine the application of Indonesian language learning in elementary schools. As well as knowing the issues and strategies used to solve these problems. The method used in this research is qualitative. This study's data were collected through interviewing grade 2 teachers at YAPITA Elementary School in Surabaya City, observation, and documentation. This study also looked at classroom lesson planning documents such as teaching modules. This study shows that teachers experience obstacles in preparing teaching modules, learning delays experienced by students, and no good application of the Indonesian language in daily communication. The influence of the environment around children also affects the level of learning success of students. The learning strategy chosen will be adjusted to the learning model in the classroom. Thus, the teacher can identify the material in advance to determine the appropriate learning model.